A reliability-based robust design optimization approach for composite structures - Carlos Conceição António (2017)
A structural reliability-based robust design optimization (RBRDO) approach that simultaneously considers minimum weight/cost, minimum strain energy and minimum sensitivity to uncertainty propagation related to robustness is presented. The trade-off between the performance target, depending on given stress, displacement, buckling and reliability constraints imposed on composite structures, against robustness, is searched. The design variables are ply angles and ply thicknesses of shell laminates, the cross section dimensions of stiffeners and the variables related to material distribution on structure. A RBRDO approach supported by multi-objective memetic algorithm is proposed